Life-Cycle Job Choice and the Demand and Supply of Entry Level Jobs: Some Evidence from the Air Force - Vany, Arthur S. De; Saving, Thomas R. (The Review of Economics and Statistics, 1982)
Arthur S. De Vany, Thomas R. Saving, Life-Cycle Job Choice and the Demand and Supply of Entry Level Jobs: Some Evidence from the Air Force, The Review of Economics and Statistics, Vol. 64, No. 3 (Aug., 1982), pp. 457-465